Violence against children: Nurses’ role in primary health care - Silva, Alane Macedo da; Góis, Amanda Regina da Silva; Justo, Alda Maria; Gama, Thereza Christina da Cunha Lima; Nascimento, Marismar Fernandes do; Carvalho, Isabella Joyce Silva de Almeida; Campos, Maria Elda Alves de Lacerda (Seven Editora, 2023)
Violence is a phenomenon that may be present in the history of some children, configuring itself as a serious public health problem, which can compromise the formation of these developing subjects. We sought to know the role of the professional nurse in cases of violence against children. This is a research with a qualitative approach, whose data collection took place through semi-structured interviews. We used the path of thematic categorical analysis that resulted in three broad categories: "Violence against children, as nurses identify"; "Conducts adopted by nurses in cases of violence" and "Limits and challenges faced by nurses". This serious problem reported here, despite its complexity, requires health professionals to take actions to cope with it, and efforts should be made to make a greater effort to understand, identify and notify the different types of maltreatment, in order to enable a registration system with reliable information regarding situations of violence against children, thus allowing forms of prevention of this social aggravation. The expansion of this study in other realities may increase the visibility of the barriers to the necessary implementation of the notification of violence against children in health services. DOI:https://doi.org/10.56238/ptoketheeducati-031